Drugs in Dermatology: Ameluz (Aminolevulinic Acid Hydrochloride). Issue 6 (November 2017) - Eng, David J.; Grigsby, Phillip M.; Jacob, Sharon E.
Abstract : ABSTRACT: A drug is a substance used to cause a physiological change in the human body. In dermatology, drugs that treat different disorders usually fall into three categories: oral, topical, and biologic medications. Topical drugs include antibacterial and antifungal creams, corticosteroids, and gels. This column will explore the mechanism of action of Ameluz as well as its efficacy, dosage, administration, adverse effects, and alternatives.